Of healthy woman [i.e. women] and horses : a thesis presented in partial fulfilment of the requirements for the degree Master in Psychology at Massey University, Turitea Campus, Palmerston North, New Zealand - Billany, Ruth Bernadette (Massey University, 2005)
This thesis addressed the relational health resources provided by horses to a group of healthy women in a small town in New Zealand. The mutualistic symbiotic interaction between humans and animals is slowly gaining credibility amongst health professionals. Although this beneficial relationship has a long past in practice, it has a relatively short history within academia and is marginalised in relation to mainstream health research. Within a salutogenic approach to health research, this study used an ethnographic methodology bending and blurring of traditional boundaries within a feminist framework. A dominant/subordinate approach to blend quantitative and qualitative research is employed, with the quantitative study as the subordinate partner. The results from a questionnaire, based on Liang, Tracy, Taylor, Williams, Jordan and Miller's (2002) relational health indices, confirm that the growth-fostering relationships horses make available to women are authenticity, engagement and empowerment. This quantitative part of the study is reported in full in the Appendices E and Q. The dominant qualitative study involved a chiasmatic procedure with two focus group discussions and two interpretative communities blending qualitative data gathering and analysis to give voice to the perspectives of women engaged in daily experiences with horses. Seventeen emergent themes are synthesised into five growth promoting qualities extending Liang et al.'s (2002) study to include a connection to other humans and connection to nature which reweaves the dichotomy between nature and culture. Further research is called for in the domain of health psychology to investigate the salutogenic effects of this reconnection with nature through sharing our lives with animals, especially horses.
Keywords: Women and horses; Human-animal relationships